Photopatternable nano-composite (SU-8/ZnO) thin films for piezo-electric applications - Kandpal, Manoj; Sharan, Chandrashekhar; Poddar, Pankaj; Prashanthi, K.; Apte, Prakash R.; Rao, V. Ramgopal (Applied Physics Letters, 2012)
Photo-curable nanocomposite material was formulated by embedding ZnO nanoparticles into a SU-8 matrix and studied for its piezoelectric properties for low cost fabrication of self-powered nanodevices. The piezoelectric coefficient of ZnO nanoparticles was observed to be ranging between 15 and 23 pm/V, which is the highest reported. These experimental studies support the recent theoretical predictions where the piezoelectric coefficients in ZnO nanoparticles were found to be higher compared to the thin films because of the surface relaxation induced volume reductions in the nanometer scale. The photo-curable property of these polymer composite films is exploited to demonstrate fabrication of a micro-cantilever test structure. (C) 2012 American Institute of Physics. [http://dx.doi.org/10.1063/1.4748575]

Spin-coatable, photopatternable magnetic nanocomposite thin films for MEMS device applications - Kandpal, Manoj; Sharan, C.; Palaparthy, V.; Tiwary, N.; Poddar, P.; Rao, V. Ramgopal (RSC Advances, 2015)
Magnetic nanomaterials' (especially metals) air stability and compatibility with standard micro-fabrication technologies are often a concern for development of MEMS-based magnetic devices. In this paper, we report an air-stable, photo-patternable and spin-coatable magnetic thin film preparation process for MEMS applications. This magnetic nanocomposite thin film was prepared by incorporating carbon capped ferromagnetic cobalt nanoparticles of dimension 20-80 nm into the SU-8 matrix. TEM, XRD and EDAX analyses were done, to investigate the crystal structure, dispersion and phase stability of the films. The SQUID magnetometry and MFM measurements of the film confirmed its magnetic response at room temperature and the retention of its magnetic properties over a period of time. The material compatibility for MEMS device applications was demonstrated through fabrication of a suspended circular membrane of radius similar to 250 mu m, having four U-shaped beams, of dimension similar to 270 x 50 mu m each. Three conventional lithography steps and a sacrificial release layer of similar to 1 mm thick oxide was used for the fabrication. The membrane was characterized by evaluating its spring constant and resonant frequency. The spring constant and resonant frequencies were estimated to be similar to 4.2 N m(-1) and similar to 29 kHz respectively. Finally, we demonstrated the actuation of the magnetic membrane by an off-chip generated magnetic field, for its possible use as a MEMS device.

H2S detection using low-cost SnO2 nano-particle Bi-layer OFETs - Surya, Sandeep G.; Ashwath, B. S. Narayan; Mishra, Sushma; Karthik, A. R. B.; Sastry, A. B.; Bhagavatula L. V. Prasad; Rangappa, Dinesh; Rao, V. Ramgopal (Sensors and Actuators B-Chemical, 2016)
In this article, a unique platform with an organic field-effect transistor (OFET) integrated with metal oxide nanoparticles for sensing of H2S gas is presented. Metal oxide nanoparticles such as SnO2 and ZnO synthesized using herbal techniques were used in the fabrication of OFETs using a bi-layer technique. The as -synthesized nanoparticles were characterized by Field Effect Scanning Electron Microscopy (FESEM), X-ray diffraction (XRD) and UV-vis Spectroscopy (UV-vis) to establish the material properties. We showed that the SnO2 based OFETs displayed better response for H2S at room temperature (25 degrees C) compared to the OFETs fabricated with ZnO. The characterization of the sensors by using extracted electrical parameters like field-effect mobility ([1), On -Current (Ion), threshold voltage (VT) and saturation current (ID]) establish the fact that the SnO2 based OFETs detect H2S gas at room temperature. Plausible mechanisms explaining the H2S gas detection by bi-layer film were discussed. On the other hand, the sensitivity of these OFETs against other reducing gases was less. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: bi-layer; H2S detection; Metal-oxide; OFETs; Sensor